Prediabetes among Nigerian adolescents: A School-based study of the prevalence, risk factors and pattern of fasting blood glucose in Ibadan, Nigeria (2016)
Pre diabetes and type 2 diabetes (T2DM) are emerging public health challenges in sub-Saharan Africa which have been given little research focus among adolescents. The behavioural and cardiometabolic factors that drive these conditions have hardly been documented among adolescents in Nigeria. A cross-sectional study was conducted to investigate the prevalence and risk factors of pre diabetes among 500 in school adolescents and their fasting blood glucose pattern in Ibadan, Nigeria. Potential factors including blood pressure, anthropometric measurements and fasting blood glucose (FBG) levels were assessed. Pre diabetes was defined as FBG between 100 –125 mg/dl. Data were analyzed using descriptive statistics and bivariate logistic regression at 5 % level of significance. The overall prevalence of pre diabetes among the adolescents was 4.0 % 95 % CI (2.2–5.7 %) and the mean FBG of adolescents was 85.3 ± 8.2. Males compared to females had significantly higher levels of FBG—mean difference [1.65:95 % CI (0.017–3.14) p = 0.03]. Factors that increased the odds for pre diabetes included frequent consumption of carbonated drinks (OR = 1.45; 95 % CI 0.46–3.30; p = 0.48), attending a private school (OR = 2.58; 95 % CI 0.77– 9.0; p= 0.66) elevated blood pressure (OR = 2.04; 95 % CI 0.57– 7.35; p= 0.57) and being overweight or obese (OR = 2.91; 95 % CI 0.38–22.3; p = 0.30). Correspondingly, while those who skipped breakfast [1.29;95 % CI (−0.23;−2.8) p = 0.096] had higher FBG, those who walked daily back from school [−2.07;95 % CI (−3.55; − 0.59) p= 0.01] had significantly lower FBG. Pre diabetes and risk factors are prevalent among the secondary school adolescents in Ibadan. Surveillance of potential risk factors through school-based screening among adolescents is crucial for prevention and early intervention